Dekonstruksi Ilmiah Triangulasi Bintang dalam Navigasi Mesir Kuno - Syam, Muhammad Adil (ELFALAKY: Jurnal Ilmu Falak, 2025)
The astronomical knowledge of Ancient Egypt has long attracted scholarly attention in the study of the history of science, yet much of its interpretation remains speculative and lacks systematic analysis. The central problem addressed in this article is the ambiguity surrounding the scientific methodology used by the ancient Egyptians to determine direction and position, particularly through the system of stellar triangulation. This study aims to deconstruct the practice of stellar triangulation based on historical data and modern scientific approaches, while also evaluating the accuracy and practical function of the method in navigation and the orientation of sacred structures of the time. The novelty of this research lies in its interdisciplinary approach, combining studies in Islamic astronomy, archaeoastronomy, and the epistemology of ancient science into a unified analysis. This article addresses two main research questions: (1) how can the method of stellar triangulation be scientifically reconstructed from Ancient Egyptian sources, and (2) how accurate and functional was this system in spatial orientation. The research uses a qualitative-descriptive method, drawing from literature review, ancient text analysis, and star modeling using astronomical software. The findings show that Ancient Egypt had a systematic understanding of stellar cycles—especially Sirius and Orion’s Belt—and employed triangulation principles for temporal and spatial orientation, albeit without modern terminology. This deconstruction offers a new perspective in rationally and scientifically appreciating the cosmological sophistication of ancient civilizations.